Preparasi dan Karakterisasi Dye-sensitized Solar Cell (DSSC) dengan Pewarna Ekstrak Jeruk: Pengaruh Variasi Komposisi Karotenoid dan Flavonoid Terhadap Efisiensi Sel Surya: Ernawita, Irwansyah, Dyah Sawitri, Ruri Agung Wahyuono - Ernawita Ernawita; Irwansyah Irwansyah; Dyah Sawitri Dyah Sawitri; Ruri Agung Wahyuono Ruri Agung Wahyuono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2017)
Dye-sensitized solar cells (DSSC) employing ZnO and citrus extracts as sensitizer were fabricated and characterized. Citrus extracts used in this study were isolated from Citrus hysterics and Citrus Auran-Tii folia (kafir lime). Infrared spectroscopy study, corroborated with HPLC and LC-MS, estimates that both citrus extracts contain a high content of lutein as carotenoids. In addition, Citrus hysteric extracts contain rich flavonoid including naringin, hesperidin, and tangeritin, while kafir lime extracts are characterized by high content of quercetin, sakuranetin, and tangeritin. The combination of different flavonoids and carotenoids in both extracts results in different optical and electronic properties. The current-voltage measurement of ZnO-based DSSC shows that the open circuit voltage (V0 c) and fill factor (FF) are unaffected upon using different dyes, i.e. V0 c == 0.340 V and FF == 0.4. The highest short circuit current (Jsc = 0.956 mA.cm-2 ) is generated in DSSC utilizing Citrus hysteric extracts and yield efficiency up to 0.122%.